2022
DOI: 10.1038/s41467-022-32195-2
|View full text |Cite
|
Sign up to set email alerts
|

In mouse chronic pancreatitis CD25+FOXP3+ regulatory T cells control pancreatic fibrosis by suppression of the type 2 immune response

Abstract: Chronic pancreatitis (CP) is characterized by chronic inflammation and the progressive fibrotic replacement of exocrine and endocrine pancreatic tissue. We identify Treg cells as central regulators of the fibroinflammatory reaction by a selective depletion of FOXP3-positive cells in a transgenic mouse model (DEREG-mice) of experimental CP. In Treg-depleted DEREG-mice, the induction of CP results in a significantly increased stroma deposition, the development of exocrine insufficiency and significant weight los… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 77 publications
0
28
1
Order By: Relevance
“…injection of DT before the induction of pancreatitis. The depletion of T regs in adult mice does not result in autoimmune disease 21. By flow cytometry (figure 5A) and immunofluorescence detection of GFP + cells in lymph nodes (figure 5B) we confirmed a significant reduction of GFP + /CD25 + T regs in DT-treated animals, whereas phosphate-buffered saline (PBS)-treated control mice showed the typical AP-induced increase of T regs (figure 5C).…”
Section: Resultsmentioning
confidence: 60%
See 1 more Smart Citation
“…injection of DT before the induction of pancreatitis. The depletion of T regs in adult mice does not result in autoimmune disease 21. By flow cytometry (figure 5A) and immunofluorescence detection of GFP + cells in lymph nodes (figure 5B) we confirmed a significant reduction of GFP + /CD25 + T regs in DT-treated animals, whereas phosphate-buffered saline (PBS)-treated control mice showed the typical AP-induced increase of T regs (figure 5C).…”
Section: Resultsmentioning
confidence: 60%
“…The depletion of T regs in adult mice does not result in autoimmune disease. 21 By flow cytometry (figure 5A) and immunofluorescence detection of GFP + cells in lymph nodes (figure 5B) we confirmed a significant reduction of GFP + /CD25 + T regs in DT-treated animals, whereas phosphatebuffered saline (PBS)-treated control mice showed the typical AP-induced increase of T regs (figure 5C). The T eff populations in spleen, GATA3 + /CD4 + Th2-cells and TBET + /CD4 + Th1-cells were significantly increased compared with control animals (online supplemental figure S10A).…”
Section: Depletion Of Tregs Stabilises the Homoeostasis Of Cd4 + T Ce...mentioning
confidence: 56%
“…Previous studies showed that the NLRP3 inflammasome is activated in pancreatic acinar cells of an acute pancreatitis mouse model and mediates pancreatic acinar cell death responses and systemic inflammation (Gao et al, 2021), and that the activity of NOD-like receptor NOD1 has a role in pancreatic inflammation in a CP mouse model (Watanabe et al, 2016). Cadps2 KO acinar cells display infiltration of CD3-positive T cells together with fibrosis, caused by αSMA-positive aPSCs in response to injury or inflammation (Hamada et al, 2022), as described in caerulein-induced CP mice Frontiers in Molecular Biosciences frontiersin.org (Nagashio et al, 2004;Glaubitz et al, 2022). In addition, we hypothesize that NLRP3 inflammation pathway may be activated in Cadps2 KO acinar cells with disperse TGN38-positive punctae.…”
Section: Discussionmentioning
confidence: 99%
“…Caerulein was obtained from Sigma Aldricht (C9026-1MG, Munich, Germany), human myeloperoxidase from Calbiochem (Cat# 475911). All antibodies used in this study had been tested and established in previous studies ( 11 , 12 , 15 ). The concentration of the antibodies was used according to the manufacturer’s instructions.…”
Section: Methodsmentioning
confidence: 99%